Strengthening and Empowering of Community Observer and User of Biomass Waste Utilization Facility in Tadukan Raga Village, Deli Serdang Regency - Sidabutar, Rivaldi; Irvan; Trisakti, Bambang; Al Fath, Muhammad Thoriq; Surya, Indra; Sinaga, Mersi Suriani; Fatimah; Vandria Alamsyah; Johannes Siregar; Stephanie Angel King (Talenta Publisher, 2024)
Biogas is renewable energy that can be used as substitute of LPG and generator fuel. One of the uses of non-B3 biomass waste into energy has been implemented in Tadukan Raga village in Sinembah Tanjung Muda (STM) Hilir District, Deli Serdang Regency, which has been operating since 2018. This facility consists of a biogas producing unit and mushroom grumpy. This biogas unit is only capable of producing biogas which can be distributed to 20 points of the house, and the mushroom grumpy is also only limited to one type of mushroom, namely straw mushrooms. Apart from that, mushroom grumpy as a container for growing straw mushrooms is done by using empty oil palm bunches mixed with cow rumen. Therefore, the University of North Sumatra Community Service Institute conducted: (1) Operational training for biomass reactors through making starters to increase biogas production in facilities for utilizing non-hazardous biomass waste into energy (2) Addition of biogas piping networks and biogas stoves to nearby residents' homes. at facilities for utilizing non-B3 biomass waste into energy (3) Training on the decomposition of non-B3 biomass waste through the cultivation of straw mushrooms at facilities for utilizing non-B3 biomass waste into energy (4) Counseling on downstreaming of straw mushroom products at facilities for utilizing non-B3 biomass waste into energy.